A new hardware design for cardiac passive acoustic localization - Civelek, Yahya. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2005., 2005)
Heart sounds contain valuable information about the function of the heart; expert clinicians can diagnose many heart disorders by listening to these sounds. One dimensional visual representation of heart sounds called phonocardiograms (PCG) are also used to facilitate the diagnosis. Although, PCG is an inexpensive, non-invasive diagnostic technique, it has been neglected until recently because of its limitations and enormous improvements in other diagnostic techniques such as ultrasonography, CT and MRI. Recently, a significant study on PCG was conducted by Y. Bahadırlar and H. Ö. Gülçür [2]; they developed a system which is composed of a specially designed multi-sensor probe in the form of a planar microphone array, precision amplifiers, filters and A/D converters, interface circuitry, a PC and special software and obtained 2-D and 3-D images of estimates of sound producing sites in the heart. The original system called CARDIOPAL (short for Cardiac Passive Acoustic Localizer) had some limitations mostly arising from relatively limited technology at the time. It had no ECG channel, the multi-sensor probe had coupling problems on non-smooth chests. Moreover it used DMA for data transmission, which made the system device-dependent.In the present thesis, a new, easy-to-use and more compact hardware for CARDIOPAL is developed. The new system (CARDIOPAL II) can work on most of the current operating systems without problems and get data more accurately in order to increase image resolution. An ECG channel is added to the system and ECG signals are acquired simultaneously with the sound signals. The acquired data is transferred to a PC using a high-speed USB 2.0 interface. Moreover, a new flexible design is developed to avoid coupling problem of the array for non-smooth chests. CARDIOPAL II is battery-powered; surface-mount technology was used for the design of all electronic circuitry to make the final system smaller, lighter, and more resistant to electromagnetic interference. The device was tested by acquiring signals coming from two point sources. The localization of these sources was achieved. The device was also tested by obtaining data from real subjects. No quality loss from the corner microphones due to the coupling problem was observed. ECG signals were acquired simultaneously and it was observed that the relationship between ECG and sound signals matched with theory.
Keywords: Phonocardiography.; Electrocardiography.; Heart -- Sounds.